Utilization of Phosphoric Acid and Lime for Stabilizing Laterite for Lateritic Bricks Production - Adekemi Loretta AYODELE; Adefemi Daniel Adekoya; Abdulhalim Oshioke Mohammed; Ayowande Oluwatosin (Institute of Research and Community Outreach - Petra Christian University, 2021)
This study investigates the use of phosphoric acid (H3PO4) and lime in stabilizing lateritic soil for lateritic bricks production. Varying percentages (0, 2, 4 and 6%) of 1 M H3PO4, 5% lime and their combinations were mixed with lateritic soil for stabilization purpose. Hollow bricks were produced from the different mixes. The bricks were cured for 7, 14 and 28 days under ambient air condition. The compressive strength (fc), bulk density (pb), dry density (pd) and water absorption rate were determined at each of the curing days while the modulus of rupture (fr) and pH were determined after 28 days. The results show a maximum fc of 0.93 N/mm2 and 0.87 N/mm2 were obtained at 5% and 4% H3PO4 stabilization. The maximum pb and pd of 15.2 kN/m3 and 14.9 kN/m3 respectively were obtained at 4% H3PO4 stabilization. The maximum fr of 0.2 N/mm2 was obtained at combined 4% H3PO4 and 5% lime stabilization while none of the bricks passed the water absorption test.